Pollution eco facts - Howell, Izzi (Howell, Izzi. Eco facts., 2020)
Investigates several modern cases of serious pollution of the air, land, and water due to human activity, and what has been done to restore the environment and prevent future pollution--including trouble with landfills, a polluted river which once got so bad it caught on fire, and the dangers of sound pollution. Includes a glossary.